1977
DOI: 10.1111/j.1365-2222.1977.tb01436.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE mediated hypersensitivity in ageing

Abstract: Summary The serum IgE concentration is significantly lower in aged as compared with young people. This is more pronounced in males than in females (P<0.05). In fifteen aged (>70 years) compared with fifteen young subjects (<40) the specific IgE antibody response to an injection of diphtheria toxoid was significantly reduced (P<0.01). The minimum concentration of anti‐IgE antibody able to induce a weal and flare reaction when injected intradermally, was comparable in the two age groups. However, the diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 14 publications
4
16
1
1
Order By: Relevance
“…ff/., 1977;Pupil & Berna, 1976). Finally, we recently reported that the specific IgE antibody response to a subcutaneous injection of diphtheria toxoid was significantly lower in old than in young non-allergic subjects (Delespesse et al, 1977). Indeed, it has been reported that the skin response to anti-IgE antibodies or to compound 48/80, a non-specific histamine-releasing factor, is decreased in old subjects, whereas the weal and flare reaction to histamine is normal (Delespesse et ai, 1977;Pupil & Berna, 1976).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…ff/., 1977;Pupil & Berna, 1976). Finally, we recently reported that the specific IgE antibody response to a subcutaneous injection of diphtheria toxoid was significantly lower in old than in young non-allergic subjects (Delespesse et al, 1977). Indeed, it has been reported that the skin response to anti-IgE antibodies or to compound 48/80, a non-specific histamine-releasing factor, is decreased in old subjects, whereas the weal and flare reaction to histamine is normal (Delespesse et ai, 1977;Pupil & Berna, 1976).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, previous studies on non-allergic humans strongly suggest that ageing is associated with a reduced ability to develop type I, IgE-mediated allergic reactions (Orren & Dowdle, 1975: Johansson, 1968Delespesse c? On the other hand, a moderate but significant ageassociated reduction of serum IgE concentration is well-documented (Orren & Dowdle, 1975;Johansson, 1968;Delespesse et al, 1977). This characteristic of the elderly is probably related to the decline of the mast cell function and the IgH antibody production.…”
Section: Introductionmentioning
confidence: 98%
“…From the present results (table IV) and from the literature [11,29] there is no doubt that the lymphocyte response to PHA is reduced in old subjects. Similar conclu sions can be reached concerning the isoag glutinin titers [22,25], the serum IgE con centration [6,16] and the specific IgE anti body response [6,14]. An age-associated reduction of IgG antibody response has been described by Roberts-Thompson et al [15] in volunteers injected with Flagellin from Salmonella Adelaide.…”
Section: Discussionmentioning
confidence: 48%
“…Varios estudios han demostrado que la IgE sé-rica total en individuos no alérgicos disminuye con la edad, 76,77 pero la relación entre la IgE total y la enfermedad alérgica persiste en los ancianos. Al respecto se ha informado que presentan con mayor frecuencia rinitis y asma cuando las cifras de este anticuerpo se encuentran elevadas.…”
Section: Alergia Y Asmaunclassified